Computational Science and High Performance Computing II The 2nd Russian-German Advanced Research Workshop, Stuttgart, Germany, March 14 to 16, 2005 - Krause, Egon; Shokin, Yurii I.; Shokina, Nina (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2006)
This volume contains 27 contributions to the Second Russian-German Advanced Research Workshop on Computational Science and High Performance Computing presented in March 2005 at Stuttgart, Germany. The workshop was organized jointly by the High Performance Computing Center Stuttgart (HLRS) and the Russian Institute for Computational Technologies (ICT SB RAS) The contributions range from computer science, mathematics and high performance computing to applications in mechanical and aerospace engineering. They show a wealth of theoretical work and simulation experience with a potential of bringing together theoretical mathematical modelling and usage of high performance computing systems presenting the state of the art of computational technologies.